2012
DOI: 10.1016/j.pedobi.2012.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Collembola diversity in the critically endangered Cape Flats Sand Fynbos and adjacent pine plantations

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues.Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited.In most cases authors are permitted to post their version of the article (e.g. in Word or Tex form) to their pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 52 publications
(68 reference statements)
2
24
0
Order By: Relevance
“…Low sampling intensity in Africa seems to be the main reason for this pattern. Based on new records and species discovered during recent systematic sampling in the Western Cape Province alone (Janion et al 2011a, b, Potapov et al 2011, Janion et al 2012, Liu et al 2012, Janion et al 2013), it is clear that many species remain to be recorded and described for this province. Given low richness documented elsewhere in South Africa the same situation is likely to be the case both there and in other African countries.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Low sampling intensity in Africa seems to be the main reason for this pattern. Based on new records and species discovered during recent systematic sampling in the Western Cape Province alone (Janion et al 2011a, b, Potapov et al 2011, Janion et al 2012, Liu et al 2012, Janion et al 2013), it is clear that many species remain to be recorded and described for this province. Given low richness documented elsewhere in South Africa the same situation is likely to be the case both there and in other African countries.…”
Section: Discussionmentioning
confidence: 99%
“…Janion et al 2011b, Potapov et al 2011, Janion et al 2012, 2013) have indicated. Owing to a recent, large and comprehensive ecological and systematic study, accompanied by DNA Barcoding (Porco et al 2012) largely focused on the country’s Western Cape Province (Bengtsson et al 2010, Janion et al 2011a, Liu et al 2012), a substantial increase in the number of species is expected. With 67 species recognised for the Western Cape from the recorded literature, the richness estimates indicating at least 6–7 times that number being present, and based on experience in other undersampled countries such as Thailand (Bedos 1994), we expect that species richness for the country will exceed 1000.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations